Extracellular adenosine triphosphate is associated with airflow limitation severity and symptoms burden in patients with chronic obstructive pulmonary disease - Hlapčić, Iva; Hulina-Tomašković, Andrea; Somborac-Bačura, Anita; Rajković, Marija Grdić; Dugac, Andrea Vukić; Popović-Grle, Sanja; Rumora, Lada (Scientific reports, 2019)
Extracellular adenosine triphosphate (eATP)-driven inflammation was observed in chronic obstructive pulmonary disease (COPD) but was not investigated in patients’ blood. Therefore, this study aimed to investigate eATP concentration in plasma of COPD patients and its association with disease severity and smoking. Study included 137 patients with stable COPD and 95 control subjects. eATP concentration was determined in EDTA plasma by luminometric method, and mRNA expression of eATP receptors P2X7R and P2Y2R was analysed by quantitative polymerase chain reaction (qPCR). eATP concentration was increased in COPD patients compared to controls (P < 0.001). Moreover, it was increasing with disease severity (GOLD 2–4) as well as symptoms burden and exacerbations history (GOLD A–D) (P < 0.05). eATP in healthy smokers differed from healthy non-smokers (P < 0.05) but was similar to GOLD 2 and GOLD A patients. eATP showed great diagnostic performances (OR = 12.98, P < 0.001) and correctly classified 79% of study participants. It demonstrated association with FEV 1 and multicomponent indices (ADO, BODEx, BODCAT, CODEx, DOSE). Regarding gene expression, P2Y2R was increased in the blood of COPD patients. Plasma eATP could become a diagnostic and/or prognostic biomarker in COPD, as it seems to be associated with patients’ condition, quality of life and disease progression.